CLINICAL AND MORPHOLOGICAL EVALUATION OF THE CONDITION OF THE LOWER SEGMENT OF THE UTERUS AFTER CESAREAN SECTION - T. A. Perepelova; M. G. Gazazyan; A. I. Bezhin; T. A. Ishunina (IRBIS LLC, 2016)
Objective. To study clinical and morphological features of lower uterine segment after cesarean section to identify the causes and risk of development non-viable scar.Materials and Мethods. The study comprised 100 pregnant women, 80 of whom had history of caesarean section (CS). These patients, according to the results of morphological studies were divided into two subgroups. The first subgroup consisted of 39 patients with signs of morphological inferiority of the scar. The second subgroup - 41 patient, who had no evident morphological changes in the myometrium. The control group consisted of 20 female first babies born through operation of the CS. Clinical criteria of insolvency of the scar was determined on the basis of the evaluation of anamnestic data, objective and ultrasound. Morphologic study of the failure scar was associated with the presence of pathological changes of connective tissue in the scar, a high degree of disorganization and disunity bundles of smooth myocytes, significant intensity and wide distribution in myometriumhydropic (vacuolar) degeneration.Results. The studied morphological criteria were significantly higher in women with morphological signs of insolvency, compared with women who underwent surgery for the first time. In most cases, identified the mismatch between morphological, clinical and sonographic signs of insolvency of the scar. Accurate can be considered only the data of macro - and microscopic examination.Conclusion. As a result of the analysis of clinical and anamnestic data were risk groups of women who had the highest probability of insolvency of the scar after the CS. To them included: a shorter interval between the CS operations (1-2 years); presence of intra - and postoperative complications after the first CS; "immature" the cervix at full-term pregnancy, as well as anomalies of birth activity among the indications to the first CS.